Thực trạng và biện pháp quản lí hoạt động làm quen với tiếng Anh của trẻ mẫu giáo: Nghiên cứu trường hợp tại thành phố Hồ Chí Minh - Trần Tú Châu Giang, Trần Tú Châu Giang; Nguyễn Trí Dũng, Nguyễn Trí Dũng; Dư Thống Nhất, Dư Thống Nhất (Tạp chí Giáo dục, 2026)
English familiarization activities contribute to the development of children’s language, cognitive abilities, and social skills, while laying a foundation for foreign language learning in the future. This study aims to examine the current situation and propose management measures for English familiarization activities for preschool children in kindergartens in Binh Chanh Commune, Ho Chi Minh City. A questionnaire survey combined with document analysis was employed to assess the current situation as a basis for proposing management measures. The findings indicate that several limitations remain, particularly regarding the awareness of a proportion of school administrators and teachers of the role and objectives of English familiarization activities, as well as a lack of coherence in planning, implementation, monitoring, evaluation, and resource mobilization. On this basis, six management measures are proposed and clearly presented in terms of objectives, content, implementation procedures, and required conditions. These measures are interrelated and mutually supportive. They serve as useful reference materials to assist kindergarten principals in Ho Chi Minh City in enhancing the effectiveness of managing English familiarization activities for preschool children in the coming period.